2004
DOI: 10.1081/drt-120030000
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Organic Emissions by Using a Multistage Drying System for Wood-Based Biomasses

Abstract: Organic emissions during the thermal drying process are strongly dependent on the drying temperature. In the traditional single stage drying system, the inlet temperature of the drying air has to be relatively high in order to keep the airflow for drying small. In the multistage drying system, the drying airflow is heated up again after the first drying stage with higher moisture content, and then again after the second, and subsequent drying stages. In this method, the drying temperatures are limited in all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Product and air flow in the same direction; exhaust air from stage 1 reheated and used in stage 2. [9] The dryer inlet air temperature per-stage is set equal to that of the optimal sorption system for equivalence. Also, the results are compared with those for two-stage adsorption drying systems with the same adsorbent in each stage: zeolite-zeolite, alumina-alumina, and silica-silica.…”
Section: Comparison With Existing Alternative Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Product and air flow in the same direction; exhaust air from stage 1 reheated and used in stage 2. [9] The dryer inlet air temperature per-stage is set equal to that of the optimal sorption system for equivalence. Also, the results are compared with those for two-stage adsorption drying systems with the same adsorbent in each stage: zeolite-zeolite, alumina-alumina, and silica-silica.…”
Section: Comparison With Existing Alternative Systemsmentioning
confidence: 99%
“…[9] In conventional multistage drying systems, the exhaust air from the earlier drying stages is reheated (to regain drying capacity lost due to moisture uptake) and reused in subsequent stages. The inlet air temperature per stage required to achieve the same moisture removal from a product is reduced as compared to a single stage dryer.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of increasing drying efficiency with the development of two-, three-or multi-stage dryers has been shown in earlier studies. These studies focus on the use of lower drying temperatures and exhaust air recycling systems, as well as adapting drying techniques to the drying rate, for example, a technique for drying below the fiber saturation point [10,[15][16][17][18][19][20]. Frodeson et al (2013) have shown, based on industrial data, that pellet plants have the potential to increase their drying capacity as well as their energy efficiency by implementing a two-step drying technique [17].…”
Section: Introductionmentioning
confidence: 99%
“…The excess steam condensate will, on the other hand, need wastewater treatment as it can contain terpenes, fatty acids, formaldehyde and other types of contamination, depending on type of biomass and drying conditions. These organic compounds are released from the biomass as it is heated [7] [8] [9] [10] [4]. A further benefit of steam drying is that since there is no oxygen present in the dryer no oxidation can occur, this in turn leads to a minimal risk of ignition during operation [6].…”
Section: Introductionmentioning
confidence: 99%